Community Participation in the Process of Making an Environmental Impact Assessment Associated with Law Number 6 of 2023 Concerning Job Creation - Mutolib, Abdul; Huda, Uu Nurul; Fauzia, Ine (JATISWARA, 2024)
This study aims to analyze community participation in the Environmental Impact Assessment (EIA) in connection with Article 22 of Law Number 6 of 2023 concerning Job Creation (Omnibus Law on Job Creation). The object of this research is changes in community participation in the process of issuing the EIA after the enactment of Omnibus Law on Job Creation. The research was carried out from December 2023 to March 2024. The research approach used a normative juridical approach using the Library Research method. Data analysis used a qualitative descriptive approach with a deductive logic approach. The study results show that the Omnibus Law on Job Creation has reduced the rights and obligations of the community in the EIA process. The initiator’s obligation to provide transparent and complete information and to be notified prior to EIA activities has been abolished so that the initiator is not required to provide complete and detailed information when development activities are to be carried out. Omnibus Law on Job Creation has eliminated the principle of Free, Prior and Informed Consent in the EIA process. Omnibus Law on Job Creation has also limited the number of people who can be involved in the EIA process. Only directly affected communities can be involved in the EIA process. Furthermore, the community’s right to object to the EIA document has been removed so that the community must accept the EIA document even though it is detrimental to society and does not support sustainable development.